Trauma, place, and transformation. (March 2019) - Sternberg, Esther M.; Engineer, Altaf; Oberman, Hester
This commentary comprises three different responses to Counted and Zock's article: "Place Spirituality: An Attachment Perspective." The first response is from Esther Sternberg, MD, who gives a psychophysiological and neuroscience critique. The second is from Altaf Engineer, PhD, from the perspective of architecture and environmental psychology, and the last response is from Hester Oberman, PhD, who gives a psychology of religion rebuttal.